Altered cardiovascular autonomic regulation in overweight children engaged in regular physical activity. Issue 6 (19th October 2012) - Lucini, Daniela; de Giacomi, Gaia; Tosi, Fabio; Malacarne, Mara; Respizzi, Stefano; Pagani, Massimo
Abstract : Overweight (OW) and obesity in children are important forerunners of cardiovascular risk, possibly through autonomic nervous system (ANS) dysregulation, while physical exercise exerts a beneficial influence. In this observational study we hypothesise that OW might influence ANS profile even in a population performing high volume of supervised exercise. We study 103 young soccer players, homogeneous in terms of gender (all male), cultural background, school, age (11.2±1 years) and exercise routine, since they all belong to the same soccer club, thus guaranteeing equality of supervised training and similar levels of competitiveness. ANS is evaluated by autoregressive spectral analysis of heart rate and systolic arterial pressure (SAP) variabilities. We estimate also the accumulated weekly Metabolic Equivalents and time spent in sedentary activities. We subdivide the entire population in two subgroups (normal weight and OW) based on the International Obesity Task Force criteria. In OW soccer players (10.7% of total group) we observe an altered profile of autonomic cardiovascular regulation, characterised by higher values of SAP (113±4 vs 100±1 mm Hg, 39.7±3 vs 66.2±10%), higher Low Frequency variability power of SAP (an index of vasomotor sympathetic regulation) (12±3 vs 4.5 mm Hg 2 ) and smaller spontaneous baroreflex gain (an index of cardiac vagal regulation) (19±3 vs 33 ±3 ms/mm Hg) (all (p<0.02)). Moreover Correlation analysis on the entire study population shows a significant link between anthropometric and autonomic indices. These data show that OW is associated to a clear autonomic impairment even in children subjected to an intense aerobic training.